Penyisihan Warna Metil Merah dengan Metode Elektrolisis Menggunakan Elektroda Aluminium - Soraya, Soraya; Sari, Ratna; Syafruddin, Syafruddin (Politeknik Negeri Lhokseumawe, 2024)
The greater development of the textile industry has an impact on environmental pollution. Textile industry waste has a high dye content and contains synthetic materials that are difficult to decompose. One of the dyes used in the textile industry is methyl red. The removal of methyl red (C15H15N3O2) color by electrolysis method is carried out to treat this industrial waste. Therefore, this study aims to determine the effect of time and voltage variations on the removal of methyl red color by electrolysis method using Aluminum (Al) as electrode. This study was conducted by contacting artificial methyl red waste with DC Power supply tools that have been connected to electrodes at a time variation of 10, 15, 20, 25, and 30 minutes with voltage variations of 2, 4, 6, 8, and volts. Color removal results with an efficiency of 98.62% were obtained in a time variation of 10 minutes with a voltage of 2 volts. However, the research results obtained are not in accordance with the theory that the longer the time and the greater the voltage the color removal will also be greater.